HARDWAREIMPLEMENTEDREAL TIME OPERATING SYSTEM (RTOS) FOR ADAPTABILITY ENHANCEMENT AND PERFORMANCE IMPROVEMENT - ONG , SOON EE (2015)
Real-Time Operating System (RTOS) is widely used in real time embedded system for computing resource sharing and management. It is commonly implemented as fun damental layer of software component in software framework. Despite of the benefit RTOS brings, it inevitably causes extra overhead and latency to the system. One of the -innovative approaches tn improve the overhead and latency is to bring the RTOS out from software framework and implement as hardware component. For past decades, researches had proved that significant performance improvement can be achieved by implementing RTOS in hardware. However, these research outcomes failed to getwide acceptance in commercial products. We postulate that the lacking of interest in com mercial community on hardware approached RTOS is due its high level of difficulty in adaptation process. Adapting hardware based RTOS in embedded system requires in-depth knowledge on operating system as well as significantamount of manpowerre sources. This makes the hardware RTOS unpopular despite of the performance offered.